2021
DOI: 10.1016/j.pmedr.2021.101356
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of tanning equipment use among Canadians

Abstract: Highlights In 2019, an estimated 3% of Canadians aged 12 or older used indoor UV tanning. Indoor tanning remained most prevalent among women, particularly at ages 18 to 34. Development of a base tan is the primary motivation for using tanning equipment. Most users have read the warnings labels at least once when “read them in the past” is considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
2
1
0
Order By: Relevance
“…Particular consideration should be given to individuals who believe that indoor tanning helps prevent sunburn, despite representing just ∼8% of all respondents, as they are at an appreciably increased risk of engaging in indoor tanning using a sunbed, and having used indoor tanning equipment in the past year. This finding agrees with a French study that described higher odds of indoor tanning for these subjects (OR 4.3, 95% CI 2.7, 6.7) 19 , and similarly, with the 2014 and 2019 Canadian Community Health Surveys 43 , 44 .…”
Section: Discussionsupporting
confidence: 92%
“…Particular consideration should be given to individuals who believe that indoor tanning helps prevent sunburn, despite representing just ∼8% of all respondents, as they are at an appreciably increased risk of engaging in indoor tanning using a sunbed, and having used indoor tanning equipment in the past year. This finding agrees with a French study that described higher odds of indoor tanning for these subjects (OR 4.3, 95% CI 2.7, 6.7) 19 , and similarly, with the 2014 and 2019 Canadian Community Health Surveys 43 , 44 .…”
Section: Discussionsupporting
confidence: 92%
“…Particular consideration should be given to individuals who believe that indoor tanning helps prevent sunburn, despite representing just ~8% of all respondents, as they are at an appreciably increased risk of engaging in indoor tanning using a sunbed and have used indoor tanning equipment in the past year. This finding agrees with a French study that described higher odds of indoor tanning for these subjects (OR 4.3, 95% CI 2.7, 6.7) [19], and similarly, with the 2014 and 2019 Canadian Community Health Surveys [43,44].…”
Section: Discussionsupporting
confidence: 92%
“…One potential reason for this decline may be the introduction of legislation on the use of tanning beds in many countries worldwide 12 . However, people in Europe and other Western countries still expose themselves to artificial UV radiation 6,13,14 . A review of European studies showed that especially women, younger people, those with skin type III/IV, employed persons, those with higher education and individuals with immigrant backgrounds use tanning beds 5 …”
Section: Introductionmentioning
confidence: 99%